Horizontal distribution of Cladocera in a subtropical lake marginal to a river - Campanelli Mortari, Rafael; Henry, Raoul [UNESP] (PAGEPress Publications, 2016)
Various abiotic and biotic factors may determine the spatial distribution patterns of Cladocera in a lake. The aim of this study was to examine the horizontal distribution of Cladocera in a lake connected to a river during low and high water phases and the abiotic factors that determine variation in their populations. Microcrustaceans were collected in integrated samples at 40 sites distributed on a lake. The mean abundance of Cladocera was around five times higher in the low water phase than in the high water phase. Only populations of Bosmina hagmanni Stingelin, 1904 and Bosminopsis deitersi Richard, 1895 predominated in the low water phase, while in the high water phase, B. hagmanni, Ceriodaphnia cornuta f. rigaudi (Sars, 1896) Diaphanosoma spinulosum Herbst, 1975 and Moina micrura Kurz, 1875 predominated at some sampling stations. The majority of cladoceran species showed an aggregated distribution in the low water phase, except B. longirostris and D. fluviatile and, B. longirostris, the only ones which presented a uniform distribution pattern in the high water phase. Most of the aggregates of cladoceran species predominated in both the dry and rainy periods on the east side of the lake due to intense easterly wind. Some cladoceran populations formed isolate aggregates in other parts of the lake and near the lake-river connection site. Canonical Correspondence Analysis (CCA) showed that the variables phosphorus, nitrogen and suspended matter (eutrophic conditions) determined distinct patterns of horizontal distribution in some cladoceran populations at some stations in the low water phase, while in others, the patterns of horizontal distribution were determined by environmental conditions as alkalinity, pH, oxygen, depth and water transparency. In the high water phase, CCA revealed that phosphorus and water transparency were positive determining factors in the distribution of some cladoceran species, while alkalinity, depth and suspended matter were negative. Our study showed that the distribution of cladoceran species may vary somewhat between the two distinct water phases depending on the micro-scale variation patterns of environmental factors.
Keywords: Aggregation index; Cladocera; Environmental factors; Marginal lake; Spatial distribution; Swarming